ChemInform Abstract: Rhodium‐Catalyzed Transnitrilation of Aryl Boronic Acids with Dimethylmalononitrile. Issue 14 (March 2016) - Malapit, Christian A.; Reeves, Jonathan T.; Busacca, Carl A.; Howell, Amy R.; Senanayake, Chris H.
Abstract: This method represents a novel approach for the preparation of aryl nitriles by using a carbon‐bound cyanating reagent which undergoes cross‐coupling with aryl boronic acids.